Tales from the crypt: intestinal niche signals in tissue renewal, plasticity and cancer - Spit, Maureen (Open Biol, 2018)
Rapidly renewing tissues such as the intestinal epithelium critically depend on the activity of small-sized stem cell populations that continuously generate new progeny to replace lost and damaged cells. The complex and tightly regulated process of intestinal homeostasis is governed by a variety of signalling pathways that balance cell proliferation and differentiation. Accumulating evidence suggests that stem cell control and daughter cell fate determination is largely dictated by the microenvironment. Here, we review recent developments in the understanding of intestinal stem cell dynamics, focusing on the roles, mechanisms and interconnectivity of prime signalling pathways that regulate stem cell behaviour in intestinal homeostasis. Furthermore, we discuss how mutational activation of these signalling pathways endows colorectal cancer cells with niche-independent growth advantages during carcinogenesis.